IMPLEMENTASI SENSOR IMU MPU6050 BERBASIS SERIAL I2C PADA SELF-BALANCING ROBOT - Beny Firman (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
The development of robotics technology more rapidly lately. Products of robotics technology is favored by many circles lately, one of them is the balancing of the robot itself or by Self-Balancing Robot. In designing a Self-Balancing Robot major success factor is the conditioning in order to keep the robot required upright position. IMU is an electronic device which measure and inform the motion of an object moving one of them Self-Balancing Robot. IMU works by detecting the state of the current acceleration in real time using the Accelerometer was to detect changes in rotation occurring on the motion of the robot using the Gyroscope. Information signal combined Accelerometer and Gyroscope sensor available on MPU6050 based IMU sensor is read by an AVRATMEGA16 Microcontroller via I2C communications. The Results of IMU data readout via I2C communication indicates the motion activity Self-Balancing Robot in measurement data parameters Pitch and Roll is 0 degrees.